Pengelolaan Pembelajaran Berbasis Learning Management System (LMS) Menggunakan Aplikasi Canva - Somawati Somawati; Andri Andri; Sepni Yanti; Munali Munali (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
One of the many applications of technology in the world of education that can be used as a learning medium in schools is Canva, an online design program that offers a variety of learning materials such as presentations, resumes, posters, brochures, pamphlets, graphics and infographics. , banners, bookmarks. , bulletins and more. Canva has features or uses for education as a creative, innovative, interactive and collaborative learning environment that makes learning easy and fun. As an application that supports technology, Canva provides a learning space for each teacher to conduct lessons using learning media. Canva offers more attractive templates in the learning process. Systems that help teachers plan curriculum, manage learning materials, manage student learning activities, manage grades, report student participation, and see grades or called Learning Management System (LMS) can be collaborated using the Canva application. In addition to teachers, students can also use Canva to present assignments, posters, poems, advertisements, and other assignments. The Canva application can be used or used through devices or laptops making it easier for teachers and students to access it anywhere and anytime. The many advantages and benefits of the Canva application make Canva very suitable to be implemented in the world of education.